2022
DOI: 10.3390/healthcare10071235
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Analysis of US COVID-19 Infected States for Vaccine Distribution

Abstract: Since December 2019, COVID-19 has been raging worldwide. To prevent the spread of COVID-19 infection, many countries have proposed epidemic prevention policies and quickly administered vaccines, However, under facing a shortage of vaccines, the United States did not put forward effective epidemic prevention policies in time to prevent the infection from expanding, resulting in the epidemic in the United States becoming more and more serious. Through “The COVID Tracking Project”, this study collects medical ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A study in Turkey investigated the impact of the pandemic on mobility and confirmed the importance of some types of mobility, such as regarding grocery stores or workplaces [67] Prediction of COVID-19 severity was evaluated in another study using longwise cluster analysis, which was evaluated as an effective way of redistributing patients based on different clinics [68]. The high accuracy of the cluster analysis was also shown in a contribution focused on the allocation of vaccines in the fight against pandemics, where individual clusters were based on the level of spread of infection [69]. Mobility during the COVID-19 pandemic depended on the degree of fear of contagion and various psychosocial factors, which were addressed by several studies [70][71][72].…”
Section: Discussionmentioning
confidence: 89%
“…A study in Turkey investigated the impact of the pandemic on mobility and confirmed the importance of some types of mobility, such as regarding grocery stores or workplaces [67] Prediction of COVID-19 severity was evaluated in another study using longwise cluster analysis, which was evaluated as an effective way of redistributing patients based on different clinics [68]. The high accuracy of the cluster analysis was also shown in a contribution focused on the allocation of vaccines in the fight against pandemics, where individual clusters were based on the level of spread of infection [69]. Mobility during the COVID-19 pandemic depended on the degree of fear of contagion and various psychosocial factors, which were addressed by several studies [70][71][72].…”
Section: Discussionmentioning
confidence: 89%